Rural Greece revisited - Burgel, Guy (The Greek Review of Social Research, 1981)
Fifteen years after a thorough survey in a Greek village, can the distance covered be measured? In real life, this distance seems enormous. Rural Greece is no longer isolated neither in its geographical situation, nor its mentalities, nor its human aspects. Has this bettered and deepened our knowledge of the Greek countryside? Or, to put the question in another way, has this reduced the economic, psychological and cultural gap between city and country? At the same time we must note the numerous melting-points shared by rural and urban Greece: whether a momentary trend or a deep-seated evolution, the «urbanization of the countryside» has made headway in a country which was neither very urbanized nor very industriali^ ed. Finally, beside regional discrepancies, social and economic disparities in the rural world have been accentuated between those who know how to benefit from such an evolution and those destroyed by this evolution. Yet, many of these unsettling influences were potentially present in the traditional rural society. Turning to history — by closely studying local sources and clearly understanding what divides Greek rural societies — should allow us to examine the demographic future of the Hellenic countryside better than many macro-economic surveys: history undoubtedly remains the key to its understanding and planning.